Bridging the gap between critical theory and critique of power? Honneth's approach to 'social negativity'. Issue 3 (2nd September 2017) - Angella, Marco
Abstract: In this paper, I will analyze Axel Honneth's theory against the background of some of the criticisms that Amy Allen levelled against it. His endeavor seems to partially compromise his ability to identify the domineering forms of power that the subject does not acknowledge consciously and affectively. I will argue that, despite some significant limitations, Honneth's theory has become increasingly able to analyze social negativity since The struggle for recognition . Also, in both defending Honneth's methodology and delimiting its scope, I aim to contribute to the debate between two understandings of power: power as 'domination' and power as 'constitution'.